Analisis Faktor Kendala Penerapan Wajib Bersertifikasi Halal di Paguyuban UMKM Kecamatan Jatirogo Kabupaten Tuban - Kristiyoningsih, Kristiyoningsih; Maulidah, Afsah Indah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Halal food is food that is permitted in Islam with the criteria of not containing haram ingredients such as pork and alcohol and is processed according to Islamic law. Halal food has many advantages, especially regarding cleanliness and food safety. The availability of halal labels becomes a regulation that aims to protect consumers and show the superiority of the products produced, with this development, the halal food industry not only focuses on Muslim consumers but also attracts the attention of non-Muslim consumers who prioritize quality and health in food. However, there are still many food business actors who have not carried out halal certification. The purpose of this study was to formulate several factors causing the slow processing of halal certification for members of the MSME association in Jatirogo District. The study was conducted on all members of the MSME association in Jatirogo District who had not carried out halal certification on the products produced by filling out a questionnaire containing a list of questions assessed using a Likert scale. The data obtained were ordinal data which were then transformed into interval data using the Successive Interval Method (MSI) which was then analyzed by "confirmatory factor analysis (CFA) " using SPSS 26.0. The results of the analysis showed that the factors constraining the slow processing of halal certification for MSME members in Jatirogo District in sequence were: 1) Knowledge of MSME actors, 2) Belief in the halalness of the products produced, 3) The assumption that consumers are less concerned about halal certification, 4) Differences in sales of halal-certified products, and 5) Halal certification processing procedures.